Measuring and monitoring quality of care in family planning: are we ignoring negative experiences? - Harris S; Reichenbach L; Hardee K (Dove Medical Press, 2016)
Shannon Harris,1 Laura Reichenbach,2 Karen Hardee2 1Public Health Consultant, Seattle, WA, USA; 2The Evidence Project, Population Council, Washington, DC, USA Abstract: Despite decades of emphasis on quality of care, qualitative research continues to describe incidents of poor quality client–provider interactions in family planning provision. Using an emerging framework on disrespect and abuse (D and A) in maternal health services, we reviewed the global published literature for quantitative tools that could be used to measure the prevalence of negative client experiences in family planning programs. The search returned over 7,000 articles, but only 12 quantitative tools included measures related to four types of D and A (non-confidential care, non-dignified care, non-consented care, or discrimination). We mapped individual measurement items to D and A constructs from the maternal health field to identify measurement gaps for family planning. We found significant gaps; current tools are not adequate for determining the prevalence or impact of negative client experiences in family planning programs. Programs need to invest in tools that describe all aspects of client experiences, including negative experiences, to increase accountability and maximize the impact of current investments in family planning programs. Keywords: quality of care, family planning programs, disrespect and abuse, client–provider interactions